The Urgency of Education Management Information System in Managing Educational Institution Data - Rahmatullah Rahmatullah; Husnil Mubarok (International Journal of Management, Innovation, and Education, 2024)
The Education Management Information System (EMIS) plays a vital role in improving the efficiency, transparency, and accountability of data management within educational institutions. As a centralized and integrated data platform, EMIS serves as a foundation for data collection, validation, and analysis to support evidence-based decision-making in education management. This study aims to examine the conceptual framework and urgency of implementing EMIS as a strategic tool for managing institutional data within the context of Islamic education under Indonesia’s Ministry of Religious Affairs. Using a qualitative research approach through a systematic literature review, this study synthesizes findings from books, policy documents, and journal articles on the development, functions, and challenges of EMIS implementation. The results show that EMIS functions as a single data gateway that consolidates institutional, academic, financial, and human resource information from various levels of education, including Raudhatul Athfal (preschool), Madrasah Ibtidaiyah (elementary), Madrasah Tsanawiyah (junior secondary), and Madrasah Aliyah (senior secondary). The use of EMIS facilitates faster, more accurate, and verifiable data processing, thus enhancing administrative performance and the quality of decision-making. Furthermore, the study emphasizes the legal and institutional framework supporting EMIS, including national regulations on data transparency and public information management. The research concludes that integrating EMIS into educational governance can promote data-driven policies, ensure accountability, and strengthen the overall management of Islamic educational institutions. This finding underscores the importance of advancing digital literacy, human resources, and system interoperability to optimize EMIS as a sustainable educational data management tool.